The Relationship Between Yoga and Spirituality: A Systematic Review of Empirical Research - Csala, Barbara; Springinsfeld, Constanze Maria; Köteles, Ferenc (Frontiers in Psychology, 2021)
Objective: Both yoga practice and spirituality are associated with beneficial mental health outcomes. Within yoga research, however, spirituality is still a widely neglected area. The present systematic review aims to explore empirical studies which do in fact investigate the relationship between yoga and spirituality in order to provide an overview and future directions for research on this topic. The review examines whether available empirical research supports an association between yoga practice and spirituality and, if so, which specific aspects of spirituality are associated with yoga practice. Methods: The systematic review followed the PRISMA guideline (Prospero registration number: CRD42020155043). Empirical studies written in English, German, or Hungarian language were selected from a database search in Google Scholar, PsycINFO, and Science Direct. A total of 30 studies met the final inclusion criteria. Results: According to the quantitative and qualitative studies reviewed, yoga practice seems to be positively associated with spirituality. This association concerns various aspects of spirituality, such as spiritual aspirations, search for insight/wisdom, integrative worldview, sense of meaning and peace, faith, hope, compassion, and happiness within. To harness the potential spiritual benefits of yoga, regular practice appears to be essential. Yoga practitioners seem to have both physical and spiritual motives for practicing. At least in Western societies, however, physical intentions are more prevalent than spiritual ones. The meaning of spirituality for yoga practitioners is also discussed. Due to risk of bias of the majority of the reviewed studies, however, outcomes must be taken with caution. Conclusions: Yoga practice is may be positively associated with several aspects of spirituality. For more evidence, further investigation of the topic is suggested. Particularly, we propose the inclusion of holistic forms of yoga practice and a comparison of Eastern and Western approaches to yoga.